Climate change, gender and aquatic food systems: call for action to address gender and social inequalities matters in the nexus - Adam, Rahma; Amani, Anamika; Kuijpers, Rob; Smits, Esther; Kruijssen, Froukje (WorldFish, 2022)
The uneven distribution of the adverse impacts of climate change on aquatic food systems is not only being felt between countries, but also within them. Particularly hard-hit are people who already experience intersecting power inequalities due to gender, socioeconomic class, age, location, ethnicity, ability, religion and caste. Among poor and marginalized groups, women are especially vulnerable to climate change due to their over-dependence on natural resources. They have limited coping and adaptive capacity owing to their multiple, competing responsibilities, further exacerbated by power inequalities. Therefore, research on the resilience of aquatic food systems to climate change must take gender and intersectional dimensions into account. Quantitative and qualitative research must transcend the household level and gender-binary (men-women) focus to explore adaptation strategies of actors in small-scale fisheries and aquaculture chains. In addition, to address entrenched power inequalities at formal, informal, local and systemic levels, it is imperative that there be more collaboration across research, interventions and policies on climate adaptation and mitigation, and on aquatic food systems. A collaborative agenda premised on the diversity inherent in small-scale fisheries and aquaculture has the potential to build resilient, equitable, efficient and effective aquatic food systems.